(untitled) (Papeles, 2017)
The configuration of a bachelor’s program in performing arts (previously a bachelor’s degree in arts education with an emphasis on dance and theater) promotes the construction of a field of study that is recent in our country. In that sense, building a legacy implies recognizing our own face in the mirror of history. Although German historiography - so important in the nineteenth century - stopped at the historical as a narrative of great stories and heroics, in the XX and XXI centuries the Annales School will investigate the fleeting, the transitory and the allowance. History is constituted by those intimate and fragmentary stories that help to consolidate the destiny of nations. Thus, our story starts with building a memory that allows us to leave sensitive evidence of the construction of a field that is vanishing nowadays: tradition. The crisis of representation, the anguish of images, the passion aroused by networks, the virtuality and the desire for permanent technological innovation, seem to leave out the constitution of the historical personality, for that reason our program promotes a controversial field between tradition and contemporaneity. The tradition, thought from a wide perspective, is not conceived as everything that remains static and probably cornered and closed in the walls of the museum. Tradition was not a becoming; it remains being as a cultural construction that defines us as humans although the speed of our present time insists on subjugate us. What we are today comes from far away, in the Hegelian sense of recognizing the historical trajectory as the unfolding of the spirit. Our traditions are legacies that remain alive and that continue up to be built in an open look to the future. Therefore, we insist on our program to leave evidences of a memory that we have built for thirty years.